Rumen impaction with foreign indigestible materials in domestic ruminants in Nigeria: A Review (2012)
Rumen impaction due to foreign, indigestible materials has become one of the major gastro-intestinal disorders in ruminant livestock causing severe loss of meat and milk production and high mortality rates. Ingested foreign bodies affect the health of animals and cause economic loss to the owner. Among other factors, the current widespread use of polythene and other non-biodegradable materials with improper waste disposal is a major predisposing factor to the development of rumen impaction. In this paper, the Nigerian situation with regard to the prevalence, reported fatalities, composition of recovered foreign materials, risk factors and clinical signs of foreign body rumen impaction are reviewed, including the clinical management approaches to the condition, the hemato-biochemical, trace element profile and pathology of the rumen in affected animals. The review also provides information on the waste disposal situation in Nigeria as it relates to the development of this condition with emphasis on its economic implications and the preventive strategies to counteract the problem of rumen impaction.